Fair allocation in graphs - Christodoulou, G; Fiat, A; Koutsoupias, E; Sgouritsa, A (Association for Computing Machinery, 2023)
We study envy freeness up to any good (EFX) in settings where valuations can be represented via a graph of arbitrary size where vertices correspond to agents and edges to items. An item (edge) has zero marginal value to all agents (vertices) not incident to the edge. Each vertex may have an arbitrary monotone valuation on the set of incident edges. We first consider allocations that correspond to orientations of the edges, where we show that EFX does not always exist, and furthermore that it is NP-complete to decide whether an EFX orientation exists. Our main result is that (EFX) allocations exist for this setting. This is one of the few cases where EFX allocations are known to exist for more than 3 agents.